2018
DOI: 10.5897/ijlp2018.0491
|View full text |Cite
|
Sign up to set email alerts
|

Potential risk factors associated with carcass contamination in slaughterhouse operations and hygiene in Oyo state, Nigeria

Abstract: Avoiding meat contamination at slaughterhouses is crucial for food safety; consumers' awareness and concern for the type of food they eat has attracted global attention and redirected research interests towards food safety. The practical hygiene in the slaughterhouse operations play key role in the safety and wholesomeness of meat. A cross sectional survey was carried out on 60 slaughterhouses in Ibadan, Oyo and Ogbomosho, in Oyo State, South Western Nigeria. A well-structured pre-tested checklist was administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…Its average elevation is estimated to be 1810 meters above sea level. The city's mean annual temperature ranges from 7.1°C to 29.7°C, whereas the annual mean temperature was 20.85°C [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Its average elevation is estimated to be 1810 meters above sea level. The city's mean annual temperature ranges from 7.1°C to 29.7°C, whereas the annual mean temperature was 20.85°C [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the WHO, FBDs in developing nations are serious because of bad hygienic food handling methods, bad understanding and absence of infrastructure [7]. This is due to the prevailing poor food handling and sanitation practices, inadequate food safety laws, weak regulatory systems, lack of financial resources, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Water suitable for human consumption is plays critical role in facilitate various slaughterhouse activities, whether in its hot or cold state. 14 At present in Iraq, the researchers have not found available national figures on the state of facilities of water supply in the slaughterhouses. As this study is one of the few studies in this field which indicated that all of small slaughterhouses had a adequacies facilities of water supply.…”
Section: Discussionmentioning
confidence: 99%